Menstrual disturbances in athletes: a focus on luteal phase defects - De Souza, M. J. (Medicine & Science in Sports & Exercise, 2003)
Subtle menstrual disturbances that affect the largest proportion of physically active women and athletes include luteal phase defects (LPD). Disorders of the luteal phase, characterized by poor endometrial maturation as a result of inadequate progesterone (P4) production and short luteal phases, are associated with infertility and habitual spontaneous abortions. In recreational athletes, the 3-month sample prevalence and incidence rate of LPD and anovulatory menstrual cycles is 48% and 79%, respectively. A high proportion of active women present with LPD cycles in an intermittent and inconsistent manner. These LPD cycles are characterized by reduced follicle-stimulating hormone (FSH) during the luteal-follicular transition, a somewhat blunted luteinizing hormone surge, decreased early follicular phase estradiol excretion, and decreased luteal phase P4 excretion both with and without a shortened luteal phase. LPD cycles in active women are associated with a metabolic hormone profile indicative of a hypometabolic state that is similar to that observed in amenorrheic athletes but not as comprehensive or severe. These metabolic alterations include decreased serum total triiodothyronine (T3), leptin, and insulin levels. Bone mineral density in these women is apparently not reduced, provided an adequate estradiol environment is maintained despite decreased P4. The high prevalence of LPD warrants further investigation to assess health risks and preventive strategies.